Fusarium Oxysporum Volatiles Enhance Plant Growth Via Affecting Auxin Transport and Signaling - Bitas, Vasileios; McCartney, Nathaniel; Li, Ningxiao; Demers, Jill; Kim, Jung-Eun; Kim, Hye-Seon; Brown, Kathleen M.; Kang, Seogchan (Frontiers in Microbiology, 2015)
Volatile organic compounds (VOCs) have well-documented roles in plant-plant communication and directing animal behavior. In this study, we examine the less understood roles of VOCs in plant-fungal relationships. Phylogenetically and ecologically diverse strains of Fusarium oxysporum, a fungal species complex that often resides in the rhizosphere of assorted plants, produce volatile compounds that augment shoot and root growth of Arabidopsis thaliana and tobacco. Growth responses of A. thaliana hormone signaling mutants and expression patterns of a GUS reporter gene under the auxin-responsive DR5 promoter supported the involvement of auxin signaling in F. oxysporum volatile-mediated growth enhancement. In addition, 1-naphthylthalamic acid, an inhibitor of auxin efflux, negated F. oxysporum volatile-mediated growth enhancement in both plants. Comparison of the profiles of volatile compounds produced by F. oxysporum strains that differentially affected plant growth suggests that the relative compositions of both growth inhibitory and stimulatory compounds may determine the degree of plant growth enhancement. Volatile-mediated signaling between fungi and plants may represent a potentially conserved, yet mostly overlooked, mechanism underpinning plant-fungus interactions and fungal niche adaption.